Development and characterization of monoclonal antibodies to Pneumocystis carinii. - Graves, D C (1986)
Hybridoma-producing monoclonal antibodies against Pneumocystis carinii were produced by the fusion of nonsecreting mouse myeloma cells (P3X63-Ag8.653) with splenocytes from BALB/c mice that had been immunized with partially purified preparations of P. carinii. Of 227 hybridoma clones producing antibodies against P. carinii, as measured by an enzyme-linked immunosorbent assay, 12 monoclonal antibodies showing the highest reactivity in the enzyme-linked immunosorbent assay were further characterized. The majority (11 of 12) of the monoclonal antibodies did not cross-react with Candida albicans, Cryptococcus neoformans, Histoplasma capsulatum, or Mycobacterium avium as determined by absorption experiments. By using the indirect immunofluorescence assay, serological reactivity was shown for these antibodies with titers ranging from 1:40 to 1:10,240. By using a competitive binding assay, these 12 monoclonal antibodies could be divided into seven groups, each group reacting with a different antigenic determinant of P. carinii. Sodium dodecyl sulfate-polyacrylamide gradient gel electrophoresis of P. carinii, followed by Western immunoblot analysis, allowed the identification of one major antigen with an apparent molecular weight of 110,000 by all 12 monoclonal antibodies. Other minor bands with molecular weights of approximately 116,000, 90,000, 55,000, and 35,000 were recognized by several of the monoclonal antibodies.